Pengaruh Model Search Solve Create and Share terhadap Computational Thinking Skills Siswa pada Pembelajaran Fisika - Sintiawati; Asep Irvan Irvani; Siti Nurdianti Muhajir (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
This study aims to analyze the effect of the search, solve, create, and share (SSCS) learning model on students' computational thinking skills in learning physics on sound waves. The method used is quantitative with a one-group pretest–posttest design. The research subjects consisted of 30 grade XI students at a high school in Brebes Regency. The research instrument was a descriptive test to measure computational thinking skills that included indicators of decomposition, pattern recognition, abstraction, and algorithmic thinking. The research instrument has been tested for validity and reliability. The validity test using Pearson correlation showed that all items had a correlation coefficient to the total score with a value of r = 0.400–0.618 and p < 0.05, so it was declared valid. The results of the reliability test using Cronbach's Alpha obtained a coefficient of α = 0.747, which indicates that the test results indicate that the instrument is quite reliable and suitable for use in research. Data were analyzed using a paired sample t-test and strengthened with the Wilcoxon signed-rank test on pretest indicators that did not meet the assumption of normality. The analysis results showed a very significant increase in CTS between the pretest and posttest (p < 0.001) in the overall CTS and for each indicator. All indicators experienced an increase with an effect size in the very large category. Based on these results, it can be concluded that the SSCS model can improve students' computational thinking skills in physics learning and is in line with the challenges of education in the 21st century.